Match activity and physiological responses during a junior female singles tennis tournament - Fernandez-Fernandez, J.; Mendez-Villanueva, A.; Terrados, N. (British Journal of Sports Medicine, 2007)
Objective: To assess physiological load in conjunction with individual patterns of match-play activity in junior female tennis players during actual singles tennis competition.